2021
DOI: 10.20945/2359-3997000000401
|View full text |Cite
|
Sign up to set email alerts
|

Cutoff point of TyG index for metabolic syndrome in Brazilian farmers

Abstract: Objective: Thus, the aim of this study was to identify the cutoff point of the TyG index for the diagnosis of insulin resistance (IR), according to two different diagnostic criteria of metabolic syndrome in a rural Brazilian population. Materials and methods: The study population consisted of 790 family farmers from 18 to 59 years old. The triglyceride-glucose index (TyG index) was calculated, and the Metabolic Syndrome was defined using the NCEP-ATPIII and IDF criteria. Mann-Whitney U test was used to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In our present study, the average TyG index value was significantly higher among subjects diagnosed with MS when compared to those without MS. In addition, the average of TyG index also increased according to the aggregation of MS criteria, and a good correlation was detected between the TyG index and different adiposity and metabolic parameters, as it was also reported by other studies [26, 27]. Additionally, our present results have shown a correlation of TyG index as good HOMA-IR with various parameters of adiposity and cardiometabolic risk related with MS. For example, abdominal obesity, determined through the waist circumference, is one of the fundamental criteria of MS.…”
Section: Discussionsupporting
confidence: 91%
“…In our present study, the average TyG index value was significantly higher among subjects diagnosed with MS when compared to those without MS. In addition, the average of TyG index also increased according to the aggregation of MS criteria, and a good correlation was detected between the TyG index and different adiposity and metabolic parameters, as it was also reported by other studies [26, 27]. Additionally, our present results have shown a correlation of TyG index as good HOMA-IR with various parameters of adiposity and cardiometabolic risk related with MS. For example, abdominal obesity, determined through the waist circumference, is one of the fundamental criteria of MS.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, there must be an association between TyG-related factors and MetS. Ferreira et al ( 67 ) identified the TyG-related factors as an important tool for predicting MetS.…”
Section: Discussionmentioning
confidence: 99%
“…In the pancreas, nutrient overload modifies the lipid metabolism, produces advanced glycation and lipoxidation end products, and leads to b-cell dysfunction (30), suggesting a close association between the glucolipid metabolism and b-cell function. TyG index is calculated using serum FBG and TG, which has been demonstrated as a novel marker for metabolic syndrome, insulin resistance, and cardiovascular diseases (13,31,32). However, the relationship between the TyG index and bcell function remains uncertain.…”
Section: Discussionmentioning
confidence: 99%